Maternal and Early-Life Nutritional Determinants of Early Adiposity Rebound in Moroccan Children (Bangladesh Journal of Medical Science, 2026)
Background Childhood obesity represents a growing global public health challenge, with early-life metabolic programming playing a critical role in shaping long-term cardiometabolic health. Early adiposity rebound (EAR), defined as a premature increase in body mass index (BMI) after its physiological nadir in early childhood, has emerged as a strong predictor of later obesity and cardiometabolic disorders. Increasing evidence suggests that nutritional and metabolic exposures during the first 1000 days of life may influence the timing of adiposity rebound. Material and methods This study aimed to investigate maternal and early-life nutritional determinants associated with EAR among Moroccan children. A cross-sectional analytical study was conducted in 2025 and included 100 mother–child pairs recruited from the Pépinière Health Center in Salé, Morocco. Anthropometric measurements and early-life exposure data were collected using structured questionnaires and maternal–child health records. Associations between EAR and potential determinants were first evaluated using chi-square tests and subsequently examined using multivariate logistic regression analysis. Results The prevalence of EAR was 38%. Early introduction of complementary feeding before six months (OR = 3.12; 95% CI: 1.35–7.21; p = 0.008), early wheat introduction (OR = 2.74; 95% CI: 1.18–6.35; p = 0.019), formula feeding (OR = 6.85; 95% CI: 2.52–18.60; p < 0.001), and low birth weight (OR = 4.96; 95% CI: 1.41–17.43; p = 0.012) were significantly associated with EAR. Maternal and perinatal factors also contributed to EAR risk, including maternal overweight at pregnancy onset (OR = 3.27; 95% CI: 1.36–7.86; p = 0.008), cesarean delivery (OR = 5.21; 95% CI: 1.82–14.88; p = 0.002), gestational diabetes (OR = 4.48; 95% CI: 1.65–12.16; p = 0.003), and limited prenatal care (OR = 3.91; 95% CI: 1.55–9.83; p = 0.040). Conclusion These findings highlight the critical role of nutritional and metabolic exposures during the first 1000 days of life in shaping early adiposity trajectories. Strengthening maternal health care and promoting appropriate infant feeding practices may therefore represent key strategies for preventing early adiposity rebound and reducing longterm obesity risk.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 742-750